Optimal Location of Thyristor-controlled-series-capacitor using Min Cut Algorithm - ThanhLong Duong; JianGang Yao; Kang Tong (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Existence of many different Operators in the new electricity has brought many challenges in the system operation and control to obtain minimum generation cost and security. With the growing demand of electricity in the competitive electricity market environment, one or more transmission lines could be overloaded, therefore causing congestion. The congestion can be eliminated /alleviated by improving transfer capability of the network. Thyristor controlled series compensators (TCSC), with its ability to directly control the power flow can be very effective to improve the operation of transmission network. This paper describes an approach for determining the most suitable locations for installing TCSC devices in order to eliminate line overloads and minimize generation costs. The proposed approach is based on the minimum cut methodology that reduces the search space and using benefit index to decide on the best locations for the TCSC. The 5-bus, IEEE 14-bus and 30-bus test systems are used to demonstrate the proposed approach. Results show that the proposed method is capable of finding the best location for TCSC installation to minimize total costs. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4423